Can FAO's measure of chronic undernourishment be strengthened? - Smith, Lisa C.; Naiken, Logan (International Food Policy Research Institute, 1998)
In its Sixth World Food Survey released at the 1996 World Food Summit, the Food and Agriculture Organization of the United Nations (FAO) reported that 841 million people in developing countries are chronically undernourished. This number and its country- and regional-level disaggregations have proved tremendously useful to countless aid agencies and researchers. In the context of a recent wave of new nationally-representative household food consumption and expenditure data, this paper examines the estimation methodology underlying this food insecurity indicator, which relies on national aggregate measures of food availability and distribution. The paper finds that the measure is methodologically biased toward national food availability and does not fully account for the effects of poverty—the most widespread cause of food insecurity in developing countries. The implications of this bias for use of the indicator in cross-country comparisons of food insecurity and for tracking changes in it over time are drawn out. The paper concludes by arguing that the time has come to review the potential for employing the new household survey data for strengthening the empirical foundations of the FAO's measure of chronic undernourishment.